Exoticism and Otherness in Gustav Mahler’s Compositions - Noémi KARÁCSONY, Mădălina Dana RUCSANDA (Editura Muzicală, 2025)
German and Austrian fin-de-siècle art was influenced by oriental and exotic arts, as proven by the visual arts of the late 19th and early 20th century, as well as by the philosophical perspectives and literary products of the period. This cultural atmosphere had a significant impact on the compositions of Gustav Mahler, whose exoticist outlook was inspired by this cultural background, as well as his Jewish heritage and philosophical beliefs. Although different in sound from French musical orientalism, where composers strive to create distinct exotic sounds through various compositional practices, the exoticism that reveals itself in the works of Gustav Mahler is often rather subtle, than clearly discernible. Mahler’s exoticism is strongly connected to the idea of otherness: the juxtaposition of contrasting styles and themes, from the tragic or sublime to the ironic and grotesque, create a novel and perplexing sound. The present research focuses mainly on Mahler’s vocal works, such as the Rückert-Lieder and the Kindertotenlieder, but also refers to the exotic features discernible in his First symphony.
Keywords: exoticism; orientalism; otherness; Mahler